Blood urea nitrogen to serum albumin ratio as a prognostic marker for 28-day mortality in atrial fibrillation: a retrospective cohort study - Huang, Yun; Wang, Guangdong; Xiang, Xia; Mei, Jun; Zhang, Chunyan; Zhang, Yaxin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe blood urea nitrogen to serum albumin ratio (BAR) has emerged as a potential prognostic marker. This study investigated its association with clinical outcomes in patients with atrial fibrillation (AF).MethodsA retrospective cohort analysis was performed using data from the MIMIC-IV 2.2 database, including 4,977 patients diagnosed with AF. The primary outcome was 28-day mortality. Cox proportional hazards models were applied to evaluate the association between BAR and mortality, and restricted cubic spline (RCS) analysis was used to explore potential non-linear relationships.ResultsOf the 4,977 patients analyzed, the 28-day mortality rate was 22.99%. Higher BAR levels were significantly associated with increased risk of mortality. Each one-unit increase in BAR was associated with a 2% higher risk of 28-day mortality (HR 1.02, 95% CI 1.01–1.03). Compared with the lowest quartile (Q1), patients in the highest quartile (Q4) had a significantly increased risk (HR 1.78, 95% CI 1.42–2.22). ROC analysis showed an area under the curve (AUC) of 0.65 for BAR in predicting 28-day mortality. Subgroup analyses confirmed the consistency and robustness of these findings across diverse clinical strata.ConclusionsBAR is an independent predictor of 28-day mortality in patients with AF. Higher BAR levels are strongly associated with worse outcomes, underscoring its potential utility as a risk stratification tool in this population.